Guiding Librarians: Rethinking Library Guides as a Staff Development Tool. Issue 1 (2nd January 2018) - Bagshaw, Anna; Yorke-Barber, Phil
Abstract: Library subject guides assist students and researchers with accessing and understanding the key resources for their subject or topic areas. From the perspective of academic institutions, subject guides showcase the key subscribed (and open access) resources available to support teaching, learning and research. They are common across university libraries but there is limited research on the benefits library guides may provide librarians themselves, especially in gaining resource knowledge during the creation and maintenance of these guides. This paper proposes the idea that library guides can also function as a staff development tool for the librarians who create and maintain them, based on the results of two surveys undertaken in late 2016 and early 2017. Results reveal the majority of respondents believe that creating library guides have improved their own knowledge of subject resources. Based on our findings, we believe that further research is required on the various techniques librarians use to gain resource knowledge, and the role that subject guides have in this process.